The Use of Negative Bias Potential for Structural Engineering of Vacuum-Arc Nitride Coatings Based on FeCoNiCuAlCrV High-Entropy Alloy - Sobol, O. V.; Andreev, A. A.; Gorban, V. F.; Meylekhov, A. A.; Postelnуk, A. A.; Stolbovoy, V. A.; Zvyagolskiy, A. V. (Sumy State University, 2018)
The effect of negative bias potential (Ub = – 40, – 110, and – 200 V) upon the deposition of multielement coatings on their composition, structure, and mechanical properties was studied. It is shown that when using a high-entropy multielement (of 7 elements) FeCoNiCuAlCrV alloy, it is possible to obtain a single-phase nitride (FeCoNiCuAlCrV)N. Nitride has an fcc crystal lattice (structural type NaCl). It has been established that with an increase in Ub in the structural state occurs transition from practically nontextured (polycrystalline) to the preferential orientation of the growth of crystallites with the [111] texture axis (at Ub = – 110 V) and [110] (at Ub = – 200 V). This is accompanied by a decrease in the lattice period, as well as a decrease in hardness and modulus of elasticity. For coatings (FeCoNiCuAlCrV) N, the highest hardness of 38 GPa is achieved by using the smallest (– 40 V) bias potential during the deposition process. It is shown that to achieve high hardness at high Ub it is necessary to increase the content in the highentropy alloy of elements with high nitride-forming ability.

Досліджено вплив негативного потенціалу зміщення (Ub = – 40, – 110 і – 200 В) при осадженні багатоелементних покриттів на їх склад, структуру і механічні властивості. Показано, що при використанні високоентропійного багатоелементного (з 7 елементів) FeCoNiCuAlCrV сплаву можна отримати однофазний нітрид (FeCoNiCuAlCrV)N. Нітрид має ГЦК кристалічну решітку (структурний тип NaCl). Встановлено, що при збільшенні Ub в структурному стані відбувається перехід від практично нетекстурованих (полікристалічне) до переважної орієнтації зростання кристалітів з віссю текстури [111] (при Ub = – 110 В) і [110] (при Ub = – 200 В). Це супроводжується зменшенням періоду решітки, а також зниженнем твердості і модуля пружності. Для покриттів (FeCoNiCuAlCrV)N найбільша твердість 38 ГПа досягається при використанні найменшого (– 40 В) потенціалу зміщення в процесі осадження. Показано, що для досягнення високої твердості при великих Ub необхідно збільшувати вміст в високоентропійном сплаві елементів з високою нітрідоутворюючою здатністю.
Використання негативного потенціалу зміщення для структурної інженерії вакуумно-дугових нітридних покриттів на основі FeCoNiCuAlCrV високоентропійного сплаву
Keywords: vacuum arc; structural engineering; bias potential; pressure; phase composition; texture; hardness; твердість; тиск; кристаліти; осадження; механічні властивості